Reduced prefrontal and orbitofrontal gray matter in female adolescents with borderline personality disorder - Is it disorder specific? - Brunner, Romuald; Henze, Romy; Parzer, Peter; Kramer, Jasmin; Feigl, Nina; Lutz, Kira; Essig, Marco; Resch, Franz; Stieltjes, Bram (NeuroImage, 2010)
There is evidence that adults with borderline personality disorder (BPD) are characterized by abnormalities in frontolimbic brain areas. In this study we aimed to determine whether brain volume alterations already exist in adolescents with BPD. Sixty female right-handed individuals (age range, 14-18 years), 20 with a DSM-IV diagnosis of borderline personality disorder, 20 patients with a DSM-IV defined current psychiatric disorder and 20 healthy control subjects were included. Groups were matched for age and IQ. Using a 3 T MRI scanner, we collected 1 mm axial sections using a three-dimensional sagittal isotropic Magnetization Prepared Rapid Acquisition Gradient Echo (MPRAGE) sequence. Images were analyzed using voxel-based morphometry (VBM). Voxel-based analysis revealed that adolescents with BPD showed reduced gray matter in the dorsolateral cortex (DLPFC) bilaterally and in the left orbitofrontal cortex (OFC) relative to healthy control subjects. Adolescent clinical control subjects displayed significantly decreased gray matter volume in the right DLPFC in comparison with healthy control subjects. No significant gray matter differences were detected between the BPD group and the clinical control group. No group differences were found in the limbic system or in any white matter structures. The present study indicates that the early morphological changes in BPD are located in the PFC. However, these changes may not be BPD specific since similar changes were found in the clinical control group. Changes in limbic brain volumes and white matter structures might occur over the course of the illness.